Effect of Materials on the Mechanical Properties of Fused Deposition Modeling Three-Dimensional Printed Products - Duy Phu Nguyen; Tu San Tran; Hai Yen Tran; Ngoc Phung Nguyen; Thong Minh Vo; Thi Hong Nga Pham; Vinh Tien Nguyen; Thanh Tan Nguyen (Journal of Technical Education Science, 2025)
This study evaluates the three-dimensional (3D) printing materials used in Fused Deposition Modeling (FDM) printing technology. 3D printing technology has been developing strongly, becoming an effective support tool in production and research. The 3D printing process involves many stages, with many parameters affecting the quality and properties of the product, in which 3D printing material is one of many essential factors affecting that process. The study conducts a comprehensive assessment of the most common materials in 3D printing technology to determine the advantages and limitations of precisely five types of materials: Polylactic acid, acrylonitrile butadiene styrene, polyethylene terephthalate glycol-modified, thermoplastic polyurethane, and acrylonitrile styrene acrylate. With 3D printing, parameters such as sintering temperature, printing speed, and layer thickness are kept constant. These parameters are applied equally to all five material samples. The experiment evaluates the tensile strength of materials. The study results provide an overview of the properties and applicability of 3D printing materials, helping to select materials suitable for specific FDM 3D printing technology applications.